PERKEMBANGAN ISLAM DI ARAB SAUDI - St. Aisyah Abbas (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2017)
The history of Islamic development in Saudi Arabia is inseparable from the historical development of Islam since the time of the Prophet, and the later Caliphate period, until entering the reign of Sa'udiyyun. Then formed the state of Saudi Arabia proclaimed by Abd. Azis ibn Abd. Rahman al-Sa'ud in 1932. The development of Islam in Saudi Arabia since the proclamation of a state by the royal system, marked by the growing understanding of Islam Wahabiah pioneered by Muhammad ibn Abd al-Wahhab. This Wahabiah is widespread and increasingly existed in Saudi Arabia, especially in the mid-19th century until the 20th century, and its development pattern is based on top down. In line with Wahhabism's development, the development of Islam in terms of institution and education is also significant in Saudi Arabia. Entering the contemporary era, the Sa'udiyah regime remains in power and the population of Muslims is increasing from time to time. Other contributing factors of Islam can thrive in Saudi Arabia as well as its historical significance as the basis of Muslims since the time of the Prophet, as well as Saudi Arabia being the terminal of various information on reform and development of Islam in other countries, including the style of reform and development of Islam in Indonesia, has something to do with Saudi Arabia as a place of learning for Indonesian Ulama in the past, and the present.